2020
DOI: 10.1055/a-0987-5902
|View full text |Cite
|
Sign up to set email alerts
|

Männliche Formen der Depression und deren Behandlung

Abstract: Halb so hohe Prävalenzraten depressiver Störungen und dreifach erhöhte Suizidraten bei Männern weisen auf die Bedeutung von Geschlechterrollen für die Präsentation und den Verlauf depressiver Störungen hin. Konformität zu traditionellen Geschlechterrollen führt bei Männern zu atypischer Symptomatik und erschwert die Identifikation depressiver Störungen und die Psychotherapieaufnahme. Implikationen für eine männerspezifische Diagnostik und Therapie werden diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
2
26
0
3
Order By: Relevance
“…Men as compared to women have approximately a 30% lower utilization of psychiatric and psychotherapeutic services [1,2]. A nationally representative sample from Germany comprised of 24,016 adults revealed that 8.1% men but 11.2% women used any form of outpatient psychiatric or psychotherapeutic service in the past year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Men as compared to women have approximately a 30% lower utilization of psychiatric and psychotherapeutic services [1,2]. A nationally representative sample from Germany comprised of 24,016 adults revealed that 8.1% men but 11.2% women used any form of outpatient psychiatric or psychotherapeutic service in the past year [3].…”
Section: Introductionmentioning
confidence: 99%
“…Vandello and Bosson (2013) experimentally showed that after experiencing masculinity threats men tend to find ways to restore it by dismissing or denying masculinity threatening information, emphasizing one's masculine traits, or using group-based prejudices for one's own masculinityenhancement (Dahl & Cook, 2020;Vandello & Bosson, 2013). Many men react with maladaptive coping strategies rooted in traditional masculine role norms leading to substance misuse, aggressive, risky, or suicidal behavior, as well as reluctance to seek counseling (Bosson & Vandello, 2011;Eggenberger et al, 2021;Rice et al, 2019;Walther et al, 2021;Walther & Seidler, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although, overall men and women experience similar levels of psychological distress, men use psychotherapy about 30% less than women (Brandstetter et al, 2017;Eggenberger et al, 2021;Rommel et al, 2018;Walther et al, 2021;Walther & Seidler, 2020). Whether this pattern differs with regard to differing psychological syndromes is, however, insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…A secure attachment organization with the therapist was shown to predict positive working alliance, more compliance and greater engagement in therapy (Diener & Monroe, 2011;Dozier, 1990;Mikulincer et al, 2013). By contrast, stronger attachment avoidance was associated with rejection of treatment providers, reduced self-disclosure, and poorer use of treatment (Dozier, 1990), which are rather typical issues in male clients (Seidler et al, 2021;Walther & Seidler, 2020), highlighting the question whether gender differences in attachment anxiety and avoidance are associated with psychotherapy use.…”
Section: Introductionmentioning
confidence: 99%